Pengaruh Promosi Digital Melalui Media Sosial TikTok Dan Kualitas Produk Terhadap Keputusan Pembelian Konsumen Pada Akun Media Sosial TikTok GD Jeans Store Di Jakarta Utara - Sylvia Rahmah; Meidiana (JAMBIS : Jurnal Administrasi Bisnis, 2026)
Abstract. This study aims to analyze the influence of digital promotion (X1) through TikTok and product quality (X2) on purchasing decisions (Y) at the GP Jeans Store TikTok account in North Jakarta. Digital promotion (X1) through TikTok is currently an effective marketing strategy, especially for young consumers from the millennial and Gen Z generations. Furthermore, product quality (X2) is also a key consideration in purchasing decisions (Y). This study used a quantitative approach with a survey method, using a questionnaire administered to 180 respondents who were active TikTok users. Data analysis was conducted using multiple linear regression to determine the simultaneous and partial effects of the two independent variables on the dependent variable. The results showed that digital promotion (X1) through TikTok and product quality (X2) had a positive and significant effect, both partially and simultaneously, on consumer purchasing decisions (Y). Therefore, the integration of digital promotion strategies (X1) and improved product quality (X2) can be key to improving consumer purchasing decisions (Y) in today's digital era. Keywords: Digital Promotion, TikTok, Product Quality, Purchasing Decision, GP Jeans Store, North Jakarta